Reflections on an Embedded Librarianship Approach: The Challenge of Developing Disciplinary Expertise in a New Subject Area. Issue 1 (2nd January 2019) - Luca, Edward Joseph
ABSTRACT: Embedded librarianship has emerged as a user-centred approach to academic library services, requiring an in-depth understanding of the education and research priorities of students and staff. User-centred approaches require the development of disciplinary expertise and engagement with the research culture of a particular subject area. This paper details the author's experiences in situating his practice within the discipline of pharmacy and discusses some of the challenges around the scale and sustainability of such specialised support. Regardless of the extent to which a librarian is 'embedded', they must see themselves as learners, too, as they develop their understanding of the disciplines they support through an ongoing process of experiencing, reflecting, conceptualising and testing in their practice.